2015
DOI: 10.1002/jps.24475
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Hydrogel Containing Silver Sulfadiazine for Antimicrobial Topical Applications

Abstract: Development and optimization of a hydrogel with impregnated silver sulfadiazine was pursued, for antimicrobial topical applications. The selected hydrogel exhibited a homogeneous appearance, with whitish colloration and devoid of any fractures or cracks. The content in impregnated silver sulfadiazine was within established limits (1%, w/w) with a standard deviation of up to 1.28%. The hydrogel presented a good characteristic in relation to release of the active antimicrobial principle, verified through swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…26 The release mechanism was described as a combination of gel erosion and drug diffusion. 42 The rapid hydration of the poloxamer and Gly resulted in a significant drug release. The gradual erosion of hydrogel offered a continuous release of AgSD in 24 hours.…”
Section: Evaluation Of the Drug Release Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The release mechanism was described as a combination of gel erosion and drug diffusion. 42 The rapid hydration of the poloxamer and Gly resulted in a significant drug release. The gradual erosion of hydrogel offered a continuous release of AgSD in 24 hours.…”
Section: Evaluation Of the Drug Release Propertiesmentioning
confidence: 99%
“…20 Thermoresponsive hydrogels possess most of the desirable characteristics to be an "ideal dressing". 42 Moreover, the unique in situ formation of thermoresponsive hydrogel enables a thorough coverage of wound site regardless of wound size, shape, and depth. Besides, a thermoresponsive hydrogel was easily applied and removed with remarkably improved compliance in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinylpyrolidone and alginate-based hydrogel-containing nanosilver has been functionally evaluated for eicient luid handling capacity and strong antimicrobial activity against all major microorganisms such as Pseudomonas, Staphylococcus, Escherichia, and Candida [113]. Jodar et al [114] demonstrated silver sulfadiazine-impregnated hydrogel for antimicrobial topical application for wound healing. Silver sulfadiazine (SSD)-impregnated hydrogel was prepared by polyvinyl alcohol (PV") and dextran blending.…”
Section: Silver Dressings In Wound Healingmentioning
confidence: 99%
“…Linear regression was used to estimate the slope of this line in g/day and WVTR (g/cm 2 .day) was calculated by dividing the slope by the area (cm 2 ). 2,4,5,18 The E. coli and S. aureus subcultures were prepared by inoculating the organisms in sterilized nutrient broth medium separately and incubated for 18-24 hrs in BOD incubator to allow the growth of bacteria. The sub cultured nutrient broth was then introduced into the Mueller Hinton Agar medium for S. aureus and E. coli separately.…”
Section: Ex-vivo Bioadhesive Strength Of Film Forming Hydrogelmentioning
confidence: 99%
“…Then the petridishes were visually inspected for observation (or not) of any growth inhibition halos. 18,19,20 The hydrogels equivalent to 4 mg of silver sulfadiazine was accurately weighed and added to 40 ml of pH 7.4 phosphate buffer as dissolution medium, maintained at 370. The electrode was immersed in the dissolution medium and the readings were noted directly from the potentiometer.…”
Section: Antimicrobial Activity Of Silver Sulfadiazinementioning
confidence: 99%